Not getting high with a little help from your friends: Social versus drug network correlates of marijuana use among YMSM. (May 2019) - Janulis, Patrick; Birkett, Michelle; Phillips II, Gregory; Mustanski, Brian
Abstract: Substantial evidence has documented the importance of social connections in shaping health and drug use behaviors among adolescents and young adults. The current study extends previous research into the associations between network characteristics and drug use behavior among young men who have sex with men (YMSM) by 1) examining multiple network characteristics, 2) simultaneously assessing multiple network types (i.e., social and drug use), and 3) examining change in network characteristics and drug use behavior over time. Data for the current study comes from RADAR, a longitudinal cohort study of YMSM. Latent growth curve models examined the change in frequency of marijuana use across four observations and individual and network correlates of this change including: demographics, drug network size, drug network density, social network size, and social network density. Baseline frequency of marijuana use was positively associated with drug network size and density, while it was inversely related to social network size and density. In addition, increasing frequency of marijuana use was associated with increases in drug network size and density, while it was associated with decreases in social network size. These findings highlight the complexity of multiple network types (e.g., drug and social) and network structures (e.g., size and density) in understanding drug use behavior among YMSM. Furthermore, as changes in drug and social networks may be indicative of changes in marijuana use, peer relationships may be especially important in understanding an individual's trajectories of marijuana use. Highlights: Drug and social networks used to model longitudinal marijuana use among YMSM Both network types associated with frequency of marijuana use at baseline Increasing drug network size and density associated with increasing marijuana use Reduction in social network size is associated with increasing marijuana use